Pengaruh Model Pembelajaran Reflektif dengan Pendekatan Matematika Realistik Bernuansa Keislaman terhadap Kemampuan Komunikasi Matematis - Putra, Fredi Ganda (Universitas Islam Raden Intan Lampung, INDONESIA, 2016)
The objective of this research was to investigate the effect of the learning model on the mathematic communication of the students. The learning models compared were the reflective learning model with mathematics realistic in Islamic nuance and the direct learning model. The type of the research was a quasi-experimental research. Its population was all of the students in grade VII in MTs Al-Khairiyah Nature in academic year 2015/2016. The size of the sample was 44 students consisted of 22 in experimental class 1 and 22 in control class 1. The instruments used were mathematics communication test on the learning material of the polyhedron. The data were analyzed by using t-test. The conclusions of the research were as there is the effect of reflective learning model with mathematics realistic in Islamic nuance resulted in a better than the direct learning model.